Study of the validity of a combined potential model using the Hybrid Reverse Monte Carlo method in Fluoride glass system - Mesli, S.M.; Habchi, M.; Kotb, M.; Xu, H. (Condensed Matter Physics, 2013)
The choice of appropriate interaction models is among the major disadvantages of conventional methods such as Molecular Dynamics (MD) and Monte Carlo (MC) simulations. On the other hand, the so-called Reverse Monte Carlo (RMC) method, based on experimental data, can be applied without any interatomic and/or intermolecular interactions. The RMC results are accompanied by artificial satellite peaks. To remedy this problem, we use an extension of the RMC algorithm, which introduces an energy penalty term into the acceptance criteria. This method is referred to as the Hybrid Reverse Monte Carlo (HRMC) method. The idea of this paper is to test the validity of a combined potential model of coulomb and Lennard-Jones in a Fluoride glass system BaMnMF₇ (M = Fe,V) using HRMC method. The results show a good agreement between experimental and calculated characteristics, as well as a meaningful improvement in partial pair distribution functions (PDFs). We suggest that this model should be used in calculating the structural properties and in describing the average correlations between components of fluoride glass or a similar system. We also suggest that HRMC could be useful as a tool for testing the interaction potential models, as well Вибiр доречних моделей взаємодiї є серед головних труднощiв стандартних методiв, таких як молекулярна динамiка (МД) i Монте Карло (МК). З iншого боку, так званий метод реверсного Монте Карло (РМК), що ґрунтується на експериментальних даних, може бути застосований без жодних мiжатомних i/чи мiжмолекулярних взаємодiй. Результати РМК супроводжуються нереалiстичними сателiтними пiками. Щоб уникнути цiєї проблеми, ми використовуємо розширення РМК алгоритму, яке вводить додатковий енергетичний член у критерiї аксептансу. Цей метод називається методом гiбридного реверсного Монте Кар-ло (ГРМК). Iдея цiєї статтi полягає у перевiрцi застосовностi об’єднаної кулонiвської i леннард-джонсiвської потенцiальної моделi до системи флюоридового скла BaMnMF₇ (M = Fe,V) з використанням методу ГРМК.
Результати показують добре узгодження мiж експериментальними i обчисленими характеристиками, а також значне покращення парцiальних парних функцiй розподiлу (ПФР). Ми припускаємо, що ця модель повинна використовуватися в обчисленнях структурних властивостей i при описi середнiх кореляцiй мiж компонентами флюоридового скла чи подiбної системи. Ми також припускаємо, що ГРМК могло б бути корисним для тестування взаємодiючих потенцiальних моделей, а також для стандартних застосувань.